Uso da terra e fragmentos de vegetação de Mata Atlântica na APA Tietê: subsídios para o planejamento ambiental e a gestão territorial. - Pinto, Bruna Gabriela de Carvalho (2014)
Considering that less than 11% of the brazilian Environmental Protection Areas have a Management Plan, the assessment of land use and the conflict in Permanent Preservation Areas can provide important results to the management of this Protected Area category, since the map of degraded Permanent Preservation Areas can be used as a guide for restoration actions. This research aimed to characterize the land use in APA Tietê, highlighting the conflict associated with Permanent Preservation Areas (Federal law n° 12.651 de 2012), in order to provide subsidies to the planning and land management. We have mapped land use through supervised automatic classification of RapidEye satellite image, and determined the land use conflicts with aid of software ArcGIS 10.2. We can conclude that APA Tietê has predominance of agricultural land uses, corresponding to 78.42% of the total protected area. This area is in critical condition to biodiversity conservation, since 76.43% of Permanent Preservation Areas consist of conflicting land uses. We have mapped 908 forest fragments, of which approximately 88% have areas smaller than 10 ha. 39.64% of these forest fragments have no neighbor fragment in a distance of 100 m. The native vegetation cover represents only 9.98% of the total area of the Environmental Protection Areas. The analysis of the hypothetical scenario showed that the restoration of Permament Preservation Areas can increase the size of the fragments and enhance landscape connectivity, in compliance with environmental legislation. Another alternative indicated to increase total vegetation cover in APA Tietê following legal increments is proposed for the restoration of the area through the establishment of Legal Reserves. In this context, through multicriteria analysis, we made a rank of all the territory of the Protected Area based on ecological relevance in order to give priority to some areas for the establishment of these protected areas. This work revealed the criticality of the current status of APA Tietê, especially towards its conservation objectives and offered alternatives, based on a scientific rigor to support the planning process of the protected area, at the local, state and national context.